2023
DOI: 10.1186/s40561-023-00248-8
|View full text |Cite
|
Sign up to set email alerts
|

Fake news detection on social media: the predictive role of university students’ critical thinking dispositions and new media literacy

Abstract: This study aimed to investigate the predictive role of critical thinking dispositions and new media literacies on the ability to detect fake news on social media. The sample group of the study consisted of 157 university students. Sosu Critical Thinking Dispositions Scale, New Media Literacy Scale, and fake news detection task were employed to gather the data. It was found that university students possess high critical thinking dispositions and new media literacies as well as high fake news detection abilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Thirdly, similar to existing research about user fact-checking behavior [43,52], we found that the more users were aware that the news creators used various techniques to depict COVID-19, the more they intended to check other users' opinions [54] of these news creators and use online tools for fact-checking. As most of our respondents were relatively young (aged up to 34 years) and probably used social media actively, it is plausible that they were skilled Information and Communication Technology (ICT) users, understanding how news for social media is produced and disseminated [43].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thirdly, similar to existing research about user fact-checking behavior [43,52], we found that the more users were aware that the news creators used various techniques to depict COVID-19, the more they intended to check other users' opinions [54] of these news creators and use online tools for fact-checking. As most of our respondents were relatively young (aged up to 34 years) and probably used social media actively, it is plausible that they were skilled Information and Communication Technology (ICT) users, understanding how news for social media is produced and disseminated [43].…”
Section: Discussionsupporting
confidence: 80%
“…Recent research provides possible solutions for the above-mentioned challenges by highlighting various literacy-oriented approaches. It recognizes information literacy [49], digital literacy [50][51][52], social media literacy [53], and news literacy [54] as some of the primary measures for tackling misinformation [36,[54][55][56][57][58]. It is relevant to the present study that news literacy equips users with knowledge of news production, consumption, and dissemination and the news environment [54].…”
Section: Introductionmentioning
confidence: 95%
“…Recent research has delved into the transformative potential of social media in enhancing students' critical thinking skills. Orhan [12] conducted a comprehensive study investigating the impact of social media integration into educational settings. Their findings illuminated the positive correlation between active engagement with social media platforms and the development of critical thinking abilities among students.…”
Section: Problem Backgroundmentioning
confidence: 99%
“…Although social networking sites were initially created to facilitate interpersonal communication and social interactions between users, these platforms have also become one of the main facilitators of misinformation 1 4 . Unfortunately, as countless studies and reports have documented, misinformation can have dire consequences for the political and social wellbeing of societies around the globe 5 8 .…”
Section: Introductionmentioning
confidence: 99%